(untitled) (Journal of Parents and Teachers, 2025)
The article refers to the arrival of spring, marking the month of flowers, the growth of trees, and gardens that can serve as models and inspiration for teachers during the school year. It also presents a series of subdivisions, including titles such as "Planting a Child," "Writing a Tree," and "Having a Book," all intertwined but with great meaning.